Comprehensiveness of online sources for patient education on hereditary hearing impairment - Duymaz, Yaşar Kemal; Tekin, Ahmet M.; D’Haese, Patrick; Şahin, Şamil; Erkmen, Burak; Cırık, Ahmet Adnan; Topsakal, Vedat (Frontiers in Pediatrics, 2023)
The present study aimed at investigating the readability of online sources on hereditary hearing impairment (HHI). In August 2022, the search terms “hereditary hearing impairment”, “genetic deafness”, hereditary hearing loss”, and “sensorineural hearing loss of genetic origin” were entered into the Google search engine and educational materials were determined. The first 50 websites were determined for each search. The double hits were removed and websites with only graphics or tables were excluded. Websites were categorized into either a professional society, a clinical practice or a general health information website. The readability tests to evaluate the websites included: Flesch Reading Ease, Flesch–Kincaid grade level, Gunning–Fog Index, Simple Measure of Gobbledygook, Coleman–Liau Index, Automated Readability Index. Twentynine websites were included and categorized as from 4 professional societies, 11 from clinical practices and 14 providing general information. All analyzed websites required higher reading levels than sixth grade. On average 12–16 years of education is required to read and understand the websites focused on HHI. Although general health information websites have better readability, the difference was not statistically significant. The readability scores of every type of online educational materials on HHI are above the recommended level indicating that not all patients and parents can comprehend the information they seek for on these websites.